1997
DOI: 10.1038/sj.dmfr.4600293
|View full text |Cite
|
Sign up to set email alerts
|

A central giant cell granuloma influenced by pregnancy.

Abstract: A case of a 17-year-old patient with exacerbation of a central giant cell granuloma of the mandible during pregnancy is reported. The possible relationship of the giant cell lesion to a pre-existing fibrous dysplasia is considered although there was lack of histological evidence.A 17-year-old healthy female patient was referred by her dentist for evaluation of a lesion in the area of a missing mandibular left third molar. The only relevant dental history was the removal of the third molars 3 years earlier. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
0
13
0
2
Order By: Relevance
“…5 In the present study, no gender predilection was found. A small female predominance was present, albeit not statistically signi®cant.…”
Section: Discussionmentioning
confidence: 59%
“…5 In the present study, no gender predilection was found. A small female predominance was present, albeit not statistically signi®cant.…”
Section: Discussionmentioning
confidence: 59%
“…Pregnancy may alter the progression of CGCG but is very unlikely to initiate a new lesion. [8] The present lesion was seen in a young female patient.…”
Section: Discussionmentioning
confidence: 96%
“…There is a distinct gender predilection, with 65% of cases affecting females. [424][425][426] The rapid growth results from stimulation of a preexisting lesion rather than initiation of a new one. The anterior part of the mandible is a favorable site, and lesions commonly cross the midline.…”
Section: Giant Cell Granulomamentioning
confidence: 99%